Young adolescents' advertising literacy and purchase intention in social network games: Influence of perspective taking and need for cognition. Issue 1 (18th August 2016) - Vanwesenbeeck, Ini; Ponnet, Koen; Walrave, Michel
Abstract: Social network games (SNGs) are popular online venues for young adolescents. The aim of this study is to examine how individual traits, need for cognition (NFC) and perspective taking (PT), are related to young‐adolescents' conceptual (i.e. understanding selling and persuasive intentions) and attitudinal (i.e. critical attitude) advertising literacy in these SNGs. The current study also examines how a child's conceptual and attitudinal advertising literacy is related to purchase intentions after seeing advertising in an SNG. In total, 781 young adolescents (aged 10–14 years) took part in our study. First, participants were shown a 5‐min video clip of an SNG including advertising. After watching the video clip, the participants completed a questionnaire about, among others, NFC, PT, conceptual advertising literacy, attitudinal advertising literacy and purchase intentions. NFC was found predictive of children's understanding of the selling and persuasive intent of SNG advertising. This means that children who score higher on the NFC scale are also more likely to have a higher conceptual knowledge of SNG advertising. PT was found to negatively influence children's critical attitude towards SNG advertising. As expected, critical attitude towards advertising was negatively related to purchase intentions. Finally, purchase intention was only partially related to conceptual advertising literacy. Copyright © 2016 John Wiley & Sons, Ltd.